Mouse siglec-1 mediates trans-infection of surface-bound murine leukemia virus in a sialic acid N-acyl side chain-dependent manner - Erikson, Elina; Wratil, Paul R.; Frank, Martin; Ambiel, Ina; Pahnke, Katharina; Pino, Maria; Azadi, Parastoo; Izquierdo-Useros, Nuria; Martinez-Picado, Javier; Meier, Chris; Schnaar, Ronald L.; Crocker, Paul R.; et al. (The journal of biological chemistry, 2015)
Siglec-1 (sialoadhesin, CD169) is a surface receptor on human cells that mediates trans-enhancement of HIV-1 infection through recognition of sialic acid moieties in virus membrane gangliosides. Here, we demonstrate that mouse Siglec-1, expressed on the surface of primary macrophages in an interferon-α-responsive manner, captures murine leukemia virus (MLV) particles and mediates their transfer to proliferating lymphocytes. The MLV infection of primary B-cells was markedly more efficient than that of primary T-cells. The major structural protein of MLV particles, Gag, frequently co-localized with Siglec-1, and trans-infection, primarily of surface-bound MLV particles, efficiently occurred. To explore the role of sialic acid for MLV trans-infection at a submolecular level, we analyzed the potential of six sialic acid precursor analogs to modulate the sialylated ganglioside-dependent interaction of MLV particles with Siglec-1. Biosynthetically engineered sialic acids were detected in both the glycolipid and glycoprotein fractions of MLV producer cells. MLV released from cells carrying N-acyl-modified sialic acids displayed strikingly different capacities for Siglec-1-mediated capture and trans-infection; N-butanoyl, N-isobutanoyl, N-glycolyl, or N-pentanoyl side chain modifications resulted in up to 92 and 80% reduction of virus particle capture and trans-infection, respectively, whereas N-propanoyl or N-cyclopropylcarbamyl side chains had no effect. In agreement with these functional analyses, molecular modeling indicated reduced binding affinities for non-functional N-acyl modifications. Thus, Siglec-1 is a key receptor for macrophage/lymphocyte trans-infection of surface-bound virions, and the N-acyl side chain of sialic acid is a critical determinant for the Siglec-1/MLV interaction.